A Comparative study on halal policy in Southeast Asian countries - Priatna, Rusdiana; Fadillah, Nurul; Ibrahim, Muhammad Yusuf; Isa, Muhammad (Universitas Airlangga, 2023)
This study aims to conduct a comparative study of halal policies in Southeast Asian countries, including Indonesia, Malaysia, Singapore, Brunei, Thailand, the Philippines and Vietnam. The focus of this research is to understand the differences and similarities in the approaches and implementation of halal policies in these countries, as well as the factors that influence the development of halal regulations at the national level. The comparative analysis method is used in this study to compare the halal policies of several countries in Southeast Asia. Data and information are obtained from various sources, including official regulations, government reports, academic publications, and other relevant documents. Each country is identified as having a halal certification body that plays a role in the process of certifying and guaranteeing product halalness. Based on the results of the author's analysis, it can be concluded that almost all member countries of Asean already have halal policy regulations which serve as guidelines for implementing halal product guarantees in their respective countries. As for countries that do not have regulations related to halal policies, such as Laos and Myanmar. However, in Myanmar, there is a halal certification service by a multinational halal certificate agency. In general, the mechanism for halal certification in ASEAN countries has the same stages, starting from registration, verification, audit, determination of halal products, issuance of halal certificates to the validity period of the halal certificate. However, each of these stages has guidelines and policies contained in each country's halal policy regulations and implemented by halal certificate institutions in each country. The validity period is also a concern because the majority of the validity period of certificates in each ASEAN country is 1 year. Indonesia is the only country in Asean that enforces halal certificates for life or for production and requires halal certificates in Indonesia.